Sosialisasi Perlindungan Hukum Hak Kekayaan Intelektual Pada UMKM Desa Balo Bone - Mashendra Mashendra; Amrun Kahar; La Ode Muhammad Karim; Hasirudin Hasri; Hayun Hayun; Eko Satria; Nabila Safira (Indonesian Journal Publisher, 2025)
The purpose of this community service activity is to facilitate a comprehensive understanding of the legal protection of Intellectual Property Rights (IPR) among Micro, Small and Medium Enterprises (MSMEs) in Balo Bone Village. This socialization was motivated by the lack of awareness and understanding of MSME actors of the importance of IPR protection in protecting their products, trademarks, and innovations from the threat of infringement. The method used consisted of interactive counseling, group discussions, and simulations of IPR registration through official government platforms. The results of this activity show that participants' understanding of the concept of intellectual property rights (IPR), the benefits of legal protection, and the technical procedures associated with IPR registration has increased. The increase in participants' understanding of Intellectual Property Rights (IPR) reached an average of 43%. Indicators of improvement include an understanding of the concept of IPR which increased by 30%, the benefits of IPR protection increased by 45%, and the technical procedures for IPR registration increased by 55%. Evaluation was carried out through pre-test, post-test, and interactive simulation. These results demonstrate the effectiveness of the socialization in increasing participants' awareness and understanding, supporting them to protect their innovations and business brands independently. It is expected that this activity will enable MSMEs in Balo Bone Village to effectively utilize intellectual property rights (IPR) protection to ensure the sustainability and competitiveness of their enterprises in local and global markets.